2010
DOI: 10.19030/jabr.v26i4.301
|View full text |Cite
|
Sign up to set email alerts
|

Variables Explaining Bank Stock Prices

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt; mso-pagination: none;"><span style="color: black; font-size: 10pt;"><span style="font-family: Times New Roman;">The purpose of this study is to examine the relationship between an index of bank common stock prices and a variety of explanatory variables including interest rates on Treasury securities of various maturities and other economic variables.<span style="mso-spacerun: yes;">&nbsp; </span>We also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…According to Dehuan (2008), the shares traded on the Shanghai Stock Exchange were affected by the operating performance indicators of the companies. Moss & Moss (2010) demonstrated that bank stock prices are sensitive to changes in interest rates. Airout & Airout (2017) mentioned that the increase in profits and reserves of banks, their capital, andtheir investments leads to the rise in the price of banks' shares in the stock exchanges.…”
Section: Performance and Share Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Dehuan (2008), the shares traded on the Shanghai Stock Exchange were affected by the operating performance indicators of the companies. Moss & Moss (2010) demonstrated that bank stock prices are sensitive to changes in interest rates. Airout & Airout (2017) mentioned that the increase in profits and reserves of banks, their capital, andtheir investments leads to the rise in the price of banks' shares in the stock exchanges.…”
Section: Performance and Share Indexmentioning
confidence: 99%
“…According to Moss & Moss (2010), there is no correlation between stock prices, trade volume, liquidity, book value, and financial leverage, and they found a positive correlation between bank stock prices, dividends per share, and earnings per share. The study by Sharma (2020) concluded that earnings per share, dividend per share, and share book value also affect share market price; earnings per share and dividend per share determine the market share price.…”
Section: Price/earnings Ratiomentioning
confidence: 99%
“…Hence, cross-sectional heterogeneity exists across banks for their interest rate exposure. Literature provided substantial evidence for stock returns exhibiting statistically significant inverse relationship with interest rate changes (Alam & Salahuddin, 2009;Asprem, 1989;Ballester, Ferrer, & Gonzalez, 2011;Ballester et al, 2009;Benink & Wolff, 2000;Kasman, Vardar, & Gokce, 2011;Kwan, 1991; J. D. Moss & G. J. Moss, 2010;Park & Choi, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interest rate and stock price effects have an influence on the variance of spread. Moss and Moss (2010) examined the relationship between bank common stock index price and the interest rate on Treasury securities. He also analyzed the correlation between interest rate term structure and bank stock prices.…”
Section: Commodity Indices Risk and Return Analysis Against Libor Benmentioning
confidence: 99%